Where traditional extinction estimates fall flat: using novel cophylogenetic methods to estimate extinction risk in platyhelminths - Mulvey, Laura; Warnock, Rachel; De Baets, Kenneth (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2022)
Today parasites comprise a huge proportion of living biodiversity and play a major role in shaping community structure. Given their ecological significance, parasite extinctions could result in massive cascading effects across ecosystems. It is therefore crucial that we have a way of estimating their extinction risk. Attempts to do this have often relied on information about host extinction risk, without explicitly incorporating information about the parasites. However, assuming an identical risk may be misleading. Here, we apply a novel metric to estimate the cophylogenetic extinction rate, Ec, of parasites with their hosts. This metric incorporates information about the evolutionary history of parasites and hosts that can be estimated using event-based cophylogenetic methods. To explore this metric, we investigated the use of different cophylogenetic methods to inform the Ec rate, based on the analysis of polystome parasites and their anuran hosts. We show using both parsimony- and model-based approaches that different methods can have a large effect on extinction risk estimation. Further, we demonstrate that model-based approaches offer greater potential to provide insights into cophylogenetic history and extinction risk.
CRIS-Team Scopus Importer:2022-09-09
Keywords: conservation; cophylogenetic extinction risk; cophylogenetics; host–parasite interactions; parasites; platyhelminths